2015
DOI: 10.1371/journal.pone.0136673
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Aptamer-Drug Adduct for Targeted Liver Cancer Therapy

Abstract: AS1411 (previously known as AGRO100) is a 26 nucleotide guanine-rich DNA aptamer which forms a guanine quadruplex structure. AS1411 has shown promising utility as a treatment for cancers in Phase I and Phase II clinical trials without causing major side-effects. AS1411 inhibits tumor cell growth by binding to nucleolin which is aberrantly expressed on the cell membrane of many tumors. In this study, we utilized a simple technique to conjugate a widely-used chemotherapeutic agent, doxorubicin (Dox), to AS1411 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 45 publications
0
43
0
Order By: Relevance
“…58 In mice xenografts, AS1411-doxorubicin conjugation has shown a specific uptake/release of drug in hepatocellular carcinoma and reduced tumor formation. 59 We found combined nucleolin-specific AS1411 and doxorubicin or etoposide treatment significantly inhibited the survival and proliferation of DLBCL cells (Figure 6a and Supplementary Figure 5). Similar results were obtained when DLBCL cells were treated with nucleolin specific nucant N6L (Figure 6b and Supplementary Figure 6).…”
Section: Discussionmentioning
confidence: 82%
“…58 In mice xenografts, AS1411-doxorubicin conjugation has shown a specific uptake/release of drug in hepatocellular carcinoma and reduced tumor formation. 59 We found combined nucleolin-specific AS1411 and doxorubicin or etoposide treatment significantly inhibited the survival and proliferation of DLBCL cells (Figure 6a and Supplementary Figure 5). Similar results were obtained when DLBCL cells were treated with nucleolin specific nucant N6L (Figure 6b and Supplementary Figure 6).…”
Section: Discussionmentioning
confidence: 82%
“…Human serum albumin nanoparticles loaded with paclitaxel were delivered with the nucleolin aptamer and shown to inhibit growth of glioma xenografts in mice relative to nontargeted nanoparticles (59). AS1411 conjugated directly to doxorubicin (Dox) was delivered intravenously in mice that had hepatocellular cancer xenografts, resulting in inhibition of tumor growth (60). Other groups have functionalized different drug carriers with AS1411 and demonstrated targeted delivery of chemotherapeutic agents in vitro (61, 62).…”
Section: Cancermentioning
confidence: 99%
“…In particular, several research groups have focused their attention on AS1411-based drug-delivery approaches, developing essentially three different kinds of systems: AS1411-drug, AS1411-drug-liposomes and AS1411-drugnanoparticle conjugates. For each of these systems some valuable examples are reported here [136][137][138][139][140].…”
Section: G4-based Aptamers As Drug Delivery Systemsmentioning
confidence: 99%
“…Le Trinh et al have crosslinked AS1411 with doxorubicin, a known chemotherapeutic agent [137]. In vivo tests in a murine xenograft model have shown that injection of the AS1411-doxorubicin adduct resulted in a reduced antitumor activity compared with free doxorubicin, but also in a significant reduction of the typical side effects associated to doxorubicin treatments, such as cardiotoxicity, nephrotoxicity and weight loss [137].…”
Section: G4-based Aptamers As Drug Delivery Systemsmentioning
confidence: 99%